Social media users' privacy limits on adult content: a case study of the Instagram account @catwomanizer - Nuraini, Rahmi; Dwiandini, Afifah; Mardhika, Herdiantyara; Sari, Prasiani Purnama; Susanto, Stephanie (The Indonesian Journal of Communication Studies, 2023)
Providing personal information can strengthen interpersonal relationships, but it can also subject individuals to judgments from the recipient and result in a loss of control over that information. The Communication Privacy Management (CPM) theory can be utilized to understand how individuals manage their personal information. This research aims to investigate how the user of the Instagram account @catwomanizer, a popular influencer who frequently shares adult and sex education content, implements privacy in the interaction of adult content on Instagram. The approach employed in this study is qualitative, using instrumental case study methodology. Based on Zoom interviews conducted with @catwomanizer and three of their followers, as well as document analysis, it was found that @catwomanizer implements five derived concepts from the CPM theory. @catwomanizer establishes privacy boundaries through two processes: content creation and content delivery. Moreover, each of these processes has its own set of filters.